Documents in European Community environmental law - Sands, Philippe, 1960-; Galizzi, Paolo (Cambridge University Press, 2006)
This is the companion volume to the second edition of Philippe Sands' Principles of International Environmental Law and Sands and Galizzi's Documents in International Environmental Law. It comprises extracts from essential EC Treaties, Regulations, Directives, Decisions and other Acts of EC institutions. EC environmental legislation represents one of the most complex and challenging legal regimes for the protection of the environment. The significant body of legislation which now exists has given rise to numerous disputes over its application and interpretation. This collection brings together the principal documents in an accessible form, providing practitioners, scholars and students with the essentials necessary to understand, advise upon and apply this body of law. Concise editorial notes summarise the main provisions of the instruments reproduced and place them in their wider context.